The Problem of Secularism and Religious Regulation: Anthropological Perspectives - Giumbelli, Emerson (Religion and society, 2013)
This article raises questions about the study of secularism, from an anthropological perspective. It begins by discussing some general references in the literature on secularism and its counterpart in Latin languages, "laicity". It then discusses the approach for defining secularism that privileges models and principles, and advocates for an analysis of the devices that produce forms of regulating the religious. The study of configurations of secularism is the outcome of a consideration of all these elements (models, principles, and devices), and has a strategic focus on ways of defining, delimiting, and managing the religious. Three cases are examined in order to illustrate this approach: France, the United States, and Brazil.